2015
DOI: 10.1093/hmg/ddv031
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of rhodopsin is necessary for its stability and incorporation into photoreceptor outer segment discs

Abstract: Rhodopsin, a G-protein coupled receptor, most abundant protein in retinal rod photoreceptors, is glycosylated at asparagines-2 and 15 on its N-terminus. To understand the role of rhodopsin's glycosylation in vivo, we generated and characterized a transgenic mouse model that expresses a non-glycosylated form of rhodopsin. We show that lack of glycosylation triggers a dominant form of progressive retinal degeneration. Electron microscopic examination of retinas at postnatal day 17 revealed the presence of vacuol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 26 publications
5
29
1
Order By: Relevance
“…2B). In control studies, we found that Rho proteins migrated through the gel as a diffuse series of bands probably composed of dimers and trimers as well as heterogeneously glycosylated protein compared to rod cell opsin [11,40-42] and is consistent with the literature [11,43]. Figs.…”
Section: Resultssupporting
confidence: 90%
“…2B). In control studies, we found that Rho proteins migrated through the gel as a diffuse series of bands probably composed of dimers and trimers as well as heterogeneously glycosylated protein compared to rod cell opsin [11,40-42] and is consistent with the literature [11,43]. Figs.…”
Section: Resultssupporting
confidence: 90%
“…97,98 In bovine rhodopsin, N-terminal glycosylation has been studied extensively, and its importance in trafficking and signaling has been demonstrated. 99,100 It was previously proposed that green cone opsin, expressed in Sf9 insect cells, is glycosylated at its N-terminal region like rhodopsin, but confirmation of this has been lacking. 37 The MS/MS analysis of green opsin reported here verified the proposed N-terminal glycosylation at asparagine residues 32 and 34.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have presented the generation and initial characterization of a novel mouse model of RP59, where we have achieved global homozygous knock-in of the K42E Dhdds mutation specifically associated with RP59 [3][4][5]. Based upon the clinical presentation of RP59 in human patients [3][4][5], as well as the demonstrable importance of dolichol-dependent protein glycosylation in maintaining the normal structure and function of the vertebrate retina [11][12][13][14], we expected to observe retinal degeneration and retinal thinning in Dhdds K42E/K42E mice, particularly in mice homozygous for the K42E mutation. This expectation was also predicated on a preliminary report [23], using a similar K42E mouse knock-in model, that claimed nearly 50% loss of OS length and reduction in ONL thickness by about two-thirds at PN 3 months of age, compared to WT mouse retinas.…”
Section: Discussionmentioning
confidence: 99%
“…to the growing Dol-PP-linked oligosaccharide chains in the ER. Mutations in rhodopsin that block its glycosylation have been shown to cause retinal degeneration in vertebrate animals [11,12]. In addition, pharmacological inhibition of protein N-glycosylation with tunicamycin has been shown to disrupt retinal photoreceptor outer segment (OS) disc membrane morphogenesis in vitro [13], as well as to cause retinal degeneration with progressive shortening and loss of photoreceptor OSs in vivo [14].…”
Section: Introductionmentioning
confidence: 99%